Pengaruh Nilai-Nilai Pancasila Terhadap Pembentukan Citra Diri Positif Mahasiswa - Rohmawati, Wati; Fitrayadi, Dinar Sugiana; Mauldy Raharja, Reza (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to determine the influence of Pancasila values on the formation of positive self-image of students, especially in the dress style of students at Sultan Ageng Tirtayasa University. This study uses a quantitative approach with a descriptive method. This study uses data obtained from respondents through questionnaire data shared by students. The population of this study is all students of Sultan Ageng Tirtayasa University from 7 faculties. The research sample of 100 people was taken using the porportionate stratified random sampling technique with each sample for the faculty level. The data analysis technique uses the Partial Least Square analysis of the SmartPLS 3.0 model. Based on the results of the hypothesis test of the original sample value of 0.826, the statistical T value shows a figure of 28.834 with a >1.96 and a P value of 0.000 or <0.05. This shows that the values of Pancasila have a positive and significant influence on the positive self-image of Sultan Ageng Tirtayasa University students. Thus, the result of the Ha hypothesis is accepted and h0 is rejected.